Easy and Effective Endoscopic Retrieval of Ingested Sharp Foreign Bodies - Leiming Xu; Chao Huang; Chunying Qu; Yi Zhang; Min Zhou; Ying Chen (Journal of Basic & Applied Sciences, 2013)
Here we reported two cases of successful removal of accidentally ingested sharp foreign body. The swallowed objects were dentures with clasps which increased the risk of gastroesophageal bleeding or perforation in both cases. After several unsuccessful attempts of removal with normal assistant apparatus, the foreign bodies were eventually retrieved by using modified ship-form semitransparent plastic bags without any complications.